Decreased function of Fas and variations of the perforin gene in adult patients with primary immune thrombocytopenia. (8th July 2016) - Boggio, Elena; Gigliotti, Casimiro L.; Rossi, Davide; Toffoletti, Eleonora; Cappellano, Giuseppe; Clemente, Nausicaa; Puglisi, Simona; Lunghi, Monia; Cerri, Michaela; Vianelli, Nicola; Cantoni, Silvia; Tieghi, Alessia; et al.
Summary: A defective switching off of the immune response is involved in several autoimmune diseases. This switching off involves Fas‐mediated apoptosis, perforin‐mediated fratricide of activated lymphocytes, and the suppressive activity of regulatory T (Treg) cells. These mechanisms are altered in autoimmune lymphoproliferative syndrome that often displays autoimmune thrombocytopenia. The aim of this research was to evaluate these mechanisms in adult patients with primary immune thrombocytopenia (ITP), compared with healthy controls. The results show that a substantial subgroup of the ITP patients displayed a defective Fas function; most of them displayed decreased Fas expression in T cells activated in vitro . Moreover, ITP patients displayed an increased frequency of rare missense variations of the PRF1 gene and decreased levels of Treg. Immunological analysis showed that levels of Interleukin (IL)10 and IL17 were decreased and marginal zone B cells were increased. Moreover, myeloid and plasmacytoid dendritic cells were decreased in ITP patients. In conclusion, in adult ITP patients, several mechanisms involved in shutting off the immune response are defective and several immunological parameters are dysregulated; these alterations may play a role in the clinical heterogeneity of the disease.